Effect of pre-treatment with deslorelin on the ovarian response of ewes superovulated with FSH - Garcia, Rodrigo [UNESP]; Filho, Rogério A. Almeida [UNESP]; Sitó-Silva, Luan [UNESP]; Denadai, Renan [UNESP]; Codognoto, Viviane [UNESP]; Salgado, Letícia [UNESP]; Brochine, Suzane [UNESP]; Oba, Eunice [UNESP] (Wiley, 2024)
This study evaluated the use of the GnRH agonist hormone, deslorelin, to control the follicular population before initiating multiple ovulation and embryo transfer (MOET) treatment. Twenty-four cross-bred Santa Inês ewes, aged between 2 and 4 years, were randomly assigned to either a control group (n = 11) or a treated group (n = 13). All ewes received an intravaginal device containing 60 mg of medroxyprogesterone acetate on day 0, and a new device on day 7, which remained in place until day 14. Additionally, the ewes were administered 125 μg of cloprostenol on day 7. The superovulatory treatment involved administering 200 mg of pFSH, divided into eight decreasing doses at 12-h intervals starting on day 12. On day 14, 300 IU of eCG was administered. In the deslorelin group, three doses of 100 μg of deslorelin were administered starting on day 3 after the insertion of the vaginal device, with subsequent doses given at 72-h and 144-h intervals. Natural mating was performed 36 h after the removal of the progesterone implant using males with proven fertility. Embryo collection took place on the 6th day after mating, and the recovered structures were quantified and evaluated for quality and developmental stage. Transrectal ultrasonography was conducted on days 12, 16 and 21 to evaluate the ovaries, specifically to assess the ovarian follicular population and the presence of the corpus luteum. Ewes in the control group had higher embryo recovery rates (p <.01) compared to the treated group (5.2 ± 0.8 vs. 1.1 ± 0.8), with differences observed primarily in the number of morulae. The number of corpus luteum observed during the laparotomy on day 21 was significantly higher (p <.01) in the control group (10.44 vs. 4.5 corpus luteum per ewe). Yet, the treated group had a significantly higher number of follicles (p <.05) on the first day of pFSH application (5.5 vs. 3.0 follicles per ewe). In conclusion, although the inclusion of deslorelin in the superovulation protocol resulted in increased synchronization of oestrus and follicle number, it did not lead to an increase in the number of corpus luteum or harvested embryos.
Keywords: follicular dynamics; GnRH analogue; ovulation; synchronization